Effectiveness of Erasmus programme in prejudice reduction: Contact theory perspective - Ajanović Edina; Çizel Beykan; Çizel Rabia (Turističko Poslovanje, 2016)
As an important contributor to higher education and tourism industry both inside and outside of the European Union, Erasmus programme provides the significant framework for many studies in academic literature. One of the important issues which Erasmus students encounter is the issue of prejudices and stereotypes between them and local students and residence. The aim of this research is to examine the successfulness of the Erasmus programme in reducing prejudice and stereotypes between Erasmus and Turkish students/residents from the perspective of contemporary knowledge on contact theory. Accordingly, the qualitative research on Erasmus students who took their course at Akdeniz University Tourism Faculty in Antalya Turkey was conducted. The three main categories were derived after the content analysis of obtained data: Erasmus students' initiative, positive as well as the negative aspects of Erasmus process. The results of this study provide new perspective on how the prejudice reduction is being examined and in which direction should individual parties in Erasmus programme work in order to improve the overall success of the same.